Addressing mental health and wellbeing among older adults in communities of color: A scoping review of community-based participatory research approaches - Tahani Dari; Ellise Nolan; Tyler Thomas (Journal of Happiness and Health, 2025)
This research explores how community-based participatory approaches can address the challenges faced by older adults in communities of color through a scoping review of 23 studies which focus on the emotional health of this population.  The authors show how an increase in older adults in communities of color is expected in the years to come, highlighting the mental health disparities faced by people in those communities and the requirement for appropriate research frameworks to address their needs.  The authors utilize a systematic review protocol (PRISMA-P) to explore the primary research question “What is the coverage of the mental health needs of older adults from communities of color using community-based participatory research (CBPR) over the last 15 years?”. The research includes an introduction to CBPR as carried out by counselors and a consideration of how CBPR can enhance equity in mental health outcomes through collaborative efforts. The researchers share methodological trends, publication trends, and recurring themes regarding barriers to mental health among older adults in communities of color as well as themes regarding benefits to using CBPR with this population. The authors also discuss implications for counseling practice, future research, and counselor educators.